2006
DOI: 10.1128/jcm.44.5.1839-1843.2006
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of the Cell Wall-Anchoring Domain of the Autolysin-Adhesin AtlE and Its Relationship to Sequence Type, as Revealed by Multilocus Sequence Typing of Invasive and Commensal Staphylococcus epidermidis Strains

Abstract: We sequenced the adhesin-cell wall-anchoring domain of the atlE gene of 49 invasive and commensal Staphylococcus epidermidis strains. We identified 22 alleles, which could be separated into two main groups: group 1 (alleles 1 and 6 to 16, 32/49 strains) and group 2 (alleles 2 to 5 and 17 to 22, 17/49 strains). Allele 1 (the type strain sequence) was by far the most prevalent (21 of 49 strains). Multilocus sequence typing showed a clear relationship between the atlE allele and the sequence type (ST), with the "… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…We found that arylomycin C 16 inhibited the secretion of four peptidoglycan hydrolases: AtlE, the SsaA-like protein encoded by SERP0318, SERP2263, and IsaA, making this the major type of protein secreted by S. epidermidis. The autolysin-adhesin AtlE is the major autolysin of S. epidermidis, and it has a well-defined role in virulence (22,49,55) and is also thought to play a role in biofilm formation through its hydrophobicity (22) and its ability to bind various plasma and matrix proteins (22,23,43). The SsaA-like protein encoded by SERP0318 has a C-terminal cysteine-and histidine-dependent aminohydrolase/peptidase (CHAP) domain and two N-terminal LysM peptidoglycan binding domains, which are commonly associated with bacterial cell wall degradation.…”
Section: Discussionmentioning
confidence: 99%
“…We found that arylomycin C 16 inhibited the secretion of four peptidoglycan hydrolases: AtlE, the SsaA-like protein encoded by SERP0318, SERP2263, and IsaA, making this the major type of protein secreted by S. epidermidis. The autolysin-adhesin AtlE is the major autolysin of S. epidermidis, and it has a well-defined role in virulence (22,49,55) and is also thought to play a role in biofilm formation through its hydrophobicity (22) and its ability to bind various plasma and matrix proteins (22,23,43). The SsaA-like protein encoded by SERP0318 has a C-terminal cysteine-and histidine-dependent aminohydrolase/peptidase (CHAP) domain and two N-terminal LysM peptidoglycan binding domains, which are commonly associated with bacterial cell wall degradation.…”
Section: Discussionmentioning
confidence: 99%
“…We used both MLST (17)(18)(19) and multilocus variable-number tandem repeat analysis (MLVA) (20)(21)(22) to study S. epidermidis strains from BJIs. We found that the shift of these strains toward greater resistance to glycopeptides is a widespread phenomenon occurring in many STs rather than the result of the spread of a small number of GRSE strains.…”
mentioning
confidence: 99%
“…The hypothesis of a parallel but independent evolution of the two lineages is to be considered in accordance with previous studies (22). Compared with the S. epidermidis atlE gene, this gene may display polymorphism in invasive and commensal strains (28). According to our result for the S. caprae atlC gene, it is tempting to speculate that this marker may constitute a major colonization factor mediating the adhesion of bacteria to bone or medical devices and that it constitutes an alternative to screening to determine which population the isolate belongs to.…”
Section: Discussionmentioning
confidence: 94%